A tree-ring δ18O series from southernmost Fuego-Patagonia is recording flavors of the Antarctic Oscillation - Meier, Wolfgang Jens-Henrik; Aravena Donaire, Juan Carlos; Jana, Ricardo; Braun, Matthias Holger; Hochreuther, Philipp; Soto-Rogel, Pamela; Griessinger, Jussi (My University, 2020)
A 154 year-long, tree-ring based stable oxygen isotope time series (delta O-18(TRC)) of the evergreen southern beech (Nothofagus betuloides) was established for the southernmost part of Patagonia. The trees grew on the terminal moraine system of the Schiaparelli Glacier (54.4 degrees S) within the windward and hyper-humid zone of the Austral Andes. The annually resolved delta O-18(TRC) record spans the common period 1861-2015 and is based on the analysis of five individually analyzed tree individuals showing a significant mean interseries correlation (r = 0.69). To date, this time series represents the worldwide southernmost chronology of tree-ring delta O-18(TRC). Variations of the delta O-18(TRC) values are significantly correlated with hydroclimatic conditions, as derived from ERA-Interim re-analysis gridded data. Negative relationships between the delta O-18(TRC)-series and relative humidity (r(OctFeb) = -0.62, p < 0.0001) or the amount of precipitation (rJan-Feb = -0.52, p < 0.0001) can be observed for the austral spring and summer seasons. In contrast, a drier environment will increase the delta O-18(TRC) as revealed by a positive influence of evaporation (r(Sep-Feb) = 0.44, p < 0.01), sea level pressure (r(Oct-Feb) = 0.56, p < 0.0001) or maximum temperature (r(Oct-Feb) = 0.43, p < 0.01). Spatial correlation maps indicate a strong supra-regional influence of climate variables on the chronology. The annular pressure seesaw, termed as Antarctic Oscillation (AAO), mostly influences climate variability within the Southern Hemisphere and is positively correlated with the delta O-18(TRC)-chronology (r(JF) = 0.61, p < 0.0001). Since our chronology, as well as a neighboring delta O-18(TRC) chronology from the Perito Moreno Glacier (50 degrees S), are showing a high correspondence in their sensitivities to climate variabilities and towards the AAO, we merged both time series into a mean chronology. This new regional mean delta O-18(TRC)-chronology is highly sensitive to variations of the AAO (r = 0.79, p < 0.0001)) and is tested for the suitability to reconstruct the AAO for the last 150 years. The reconstructed time series of the AAO reveals an increasing trend towards more positive index values, which is associated with an amplification in the amount of precipitation and wind speed in southernmost South America.
Keywords: tree-ring delta o-18; southern patagonia; antarctic oscillation (aao); climate reconstruction; nothofagus betuloides; schiaparelli glacier; *corresponding author